VULNERABILITY OF WEATHER ON COVID-19 PANDEMIC IN WEST JAVA, INDONESIA - Tosepu, Ramadhan; Effendy, Devi Savitri; Ahmad, La Ode Ali Imran; Lestari, Hariati; Bahar, Hartati; Asfian, Pitrah; Sakka, Ambo (Public Health of Indonesia, 2020)
Background: COVID-19 is a pandemic that spreads very fast. Until now, COVID-19 has spread in 207 countries.Objective: This study aimed to analyze the correlation between weather factors and COVID-19 in West Java, Indonesia. This study used a secondary data analysis of weather data from the Meteorological Department of the Republic of Indonesia and surveillance of COVID-19 from the Ministry of Health of the Republic of Indonesia. The weather has five components, including minimum temperature (0C), maximum temperature (0C), temperature average (0C), humidity (%), amount of rainfall (mm), and wind speed (m/s). Data were analyzed using Spearman's rank correlation test.Result: Of the weather components, only temperature average (r = 0.545; p <0.001) and humidity (r = -0.500; p <0.001) significantly correlated with COVID-19.Conclusion: The results can be used to decrease the pandemic of COVID-19 in Indonesia.